The ‘Useful Man’ in the Political System of the Polish-Lithuanian Commonwealth of the Vasas – New Perspectives and Methodological Problems in Research into the Careers of Małopolska Noblemen - Kwiatek, Agata (Kwartalnik Historyczny, 2024)
In the article I point to the need for conducting research into the political careers of activists from the lesser nobility, whose families were not part of the power elite. In contemporary historiography, lesser nobility activists have only attracted the attention of historians to a limited extent. Yet the development of research and the availability of sources have made it possible to carry out a broader analysis, encompassing activists from the lesser nobility who stood out by virtue of the level of their involvement in the country’s political life.